Sediment Analysis of Shelar Lake, Maharashtra (Global Journal of Science Frontier Research, 2014)
The present paper deals with the physico-chemical properties of bottom sediment of a fresh water lake in which fishing is carried out. The soil of the lake under study was found to contain 35 % sand followed by 25% silt and 40 % clay. Thus the bottom soil was clayed loam in texture. The colour of the soil was black. The pH, conductivity, organic carbon, inorganic phosphate and nitrate were measured seasonally for two years. The water retention capacity of soil was observed as 47 % indicating favorable condition for fish culture practices as well as the chemical parameters which were complementary to it.
Keywords: sediment; productivity; fresh water; fishing